2015
DOI: 10.21283/2376905x.3.46
|View full text |Cite
|
Sign up to set email alerts
|

Heritage and L2 processing of person and number features: Evidence from Spanish subject-verb agreement

Abstract: EN This article reports on a study, with online measures, which investigated the processing of subject-verb (SV) agreement sentences by one group of heritage Spanish speakers (HSs), two groups of L2 learners of Spanish (L1 English) and one group of traditional Spanish native speakers. Experimental SV sentences manipulated person and number features with subjects and verbs in the present tense. Between-group statistical analyses indicated differential processing between the heritage and the L2 groups. The herit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
14
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 25 publications
1
14
0
Order By: Relevance
“…In contrast, other online studies found no AoA effects. For example, advanced early bilinguals and late bilinguals of Spanish were more sensitive to adjacent than non-adjacent SV number disagreement with present tense verbs in Spanish (Foote 2011), and both groups showed delayed sensitivity effects (Rodríguez and Reglero 2015) in a non-cumulative, selfpaced reading task. However, Rodríguez and Reglero mixed person and number violations (e.g., *tú lavan 'you-2ndperson-singular wash-3rdperson-plural').…”
Section: Aoa Effects On Morphosyntactic Processing In Early and Late Bilingualsmentioning
confidence: 96%
See 3 more Smart Citations
“…In contrast, other online studies found no AoA effects. For example, advanced early bilinguals and late bilinguals of Spanish were more sensitive to adjacent than non-adjacent SV number disagreement with present tense verbs in Spanish (Foote 2011), and both groups showed delayed sensitivity effects (Rodríguez and Reglero 2015) in a non-cumulative, selfpaced reading task. However, Rodríguez and Reglero mixed person and number violations (e.g., *tú lavan 'you-2ndperson-singular wash-3rdperson-plural').…”
Section: Aoa Effects On Morphosyntactic Processing In Early and Late Bilingualsmentioning
confidence: 96%
“…Contrarily, other studies show that intermediate and advanced late bilinguals are insensitive to SV violations. For intermediate late bilinguals, self-paced reading data showed that English-Spanish late bilinguals (Rodríguez and Reglero 2015;VanPatten et al 2012) and Chinese-English late bilinguals (Yao and Chen 2017) were insensitive to SV person-number violations (but VanPatten et al found that they were sensitive to VS violations in which verb tense information is not redundant). Additionally, ERP data revealed that intermediate French-English late bilinguals processed adjacent and nonadjacent SV number violations as semantic rather than morphosyntactic like French natives (Reichle et al 2013).…”
Section: Proficiency Effects On Morphosyntactic Processing In Early and Late Bilingualsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies that have analyzed the linguistic performance of young HSs usually compare them to the performance of monolingual peers [2,11,18]. Traditional native speakers have been used as a control group in the L1, since they have grown up monolingual with formal instruction in their native language.…”
Section: Heritage Grammatical Knowledge: Variability In Early and Latmentioning
confidence: 99%